Love for Prophet Muhammad (Part One): a profound inspiring love - Hasan, Md. Mahmudul (OnIslam.net, 2008)
Love is defined as a feeling or disposition of deep affection or fondness for someone, typically arising from a recognition of attractive qualities, from natural affinity, or from sympathy, and manifesting itself in concern for the other's welfare and pleasure in his or her presence (Oxford English Dictionary). Prophet Muhammad (peace and blessings be upon him) had a profound love for humanity. Throughout centuries, Muslims have had a deep, passionate love for him. The love harbored in the hearts of Muslims remains a source of inspiration, a factor of unity, and a leveler of differences among them. Indeed, this love is based on the love of Almighty Allah and on the supreme message of Islam.